Speed and power : toward an expeditionary Army - Peltz, Eric, 1968-; Halliday, John M. (John Michael), 1945-; Bower, Aimee; Rand eBooks (Santa Monica, CA : RAND, 2003)
This report explores ways in which the Army might improve its ability to contribute to the prompt, global power-projection capability of the United States, that is, the strategic responsiveness of early-entry forces in situations where time is critical. Focusing on the Army's new Stryker Brigade Combat Team, this report begins by analyzing options, given existing technology, for improving the deployment time of Army units. Then it examines how the Army might improve its ability to facilitate the rapid-deployment initiation of joint, mission-tailored packages of capabilities. In essence, there are two problems: initiating deployment of the right force capabilities and then getting these capabilities where they need to be as quickly as possible. Specific opportunities examined in the report include forward basing, new concepts in prepositioning, significant but often underappreciated opportunities in process improvement, and speeding the delivery of initial operating capabilities through deployment phasing and improved planning. Further, the research offers an approach for leveraging force modularity concepts to transition to a capabilities-based rapid mission force-tailoring construct.
Introduction -- The Deployment System and Modeling Assumptions -- Leveraging the Deployment Tradespace to Improve Strategic Responsiveness -- Rapidly Providing Mission-Tailored Force Packages -- Conclusions and Recommendations.
"Arroyo Center."
Includes bibliographical references (p. 81-83).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Army -- Combat sustainability; United States. -- Army -- Field service; United States. -- Army -- Foreign service; Airlift, Military -- United States; Deployment (Strategy); Operational readiness (Military science); Unified operations (Military science); Electronic books